033: BUILDING HEALTH RESEARCH IN THE UNIVERSITY OF THE PHILIPPINES (UP) FROM THE GROUND UP. (24th August 2015) - A, Edna Estifania
Abstract : Background: The health of the nation is under siege by a myriad of factors – food insufficiency, lack of policies responsive to the health of the majority poor, climate change, poor social determinants of health, and lifestyle that puts health at risk, among others. As a response, UP through the Emerging Interdisciplinary Research (EIDR) initiative, is creating an enabling research environment for health, among others. Objectives: The main goal of EIDR is to support emerging and interdisciplinary researches that can address national problems, including health using various disciplinal perspectives. To do this, EIDR provides seed research funds, lays the groundwork to establish a research culture in UP, promotes interdisciplinary and intercampus research interactions and activities, and supports the creation of value networks from basic to applied research to produce discoveries and innovations that can be developed into useful, patentable and marketable products and services. Methods: EIDR focuses on emerging studies that underscore an anticipatory approach to interventions as new opportunities, problems, natural phenomena develop and evolve. EIDR adopts an interdisciplinary approach as experts in various disciplines working together can provide the long-term, multi-faceted, more effective solutions to the complex problems we face today. Result: The EIDR has supported 13 diverse health related research out of 25 projects, including, among others, researches on infectious diseases such as tuberculosis; on challenges due to urbanization such as drug addiction; and innovative models on community health and gendered universal health care affecting low-income sections of society. Conclusion: UP EIDR has redefined the role of academia as a source of innovation in health research and development, involving recognized experts/scientific researchers in providing solutions to national and local health problems. Through various perspectives, an integration of health goals is achieved.